1999
DOI: 10.1111/1468-2273.00137
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Higher Education in Scotland: A Geographic and Social Analysis

Abstract: In this paper we relate participation in full-time Higher Education in Scotland to the geographic and social characteristics of the areas where people reside. National data on students at Higher Education institutions in all parts of the UK are used to calculate the rates, with areas of residence defined by their addresses at the times of applying to the institutions. Population data and the social characteristics of the areas were derived from the 1991 Census. The smallest geographic area considered was the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Those from less advantaged backgrounds, for example, may be more likely to enter higher education later in life. However, Johnston et al (1999) found that the addition of mature students into their geo-demographic analysis of participation did not equalise the gap in entry rates. An important barrier to the inclusion of older entrants in the analysis is the lack of available data on those aged over 21.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Those from less advantaged backgrounds, for example, may be more likely to enter higher education later in life. However, Johnston et al (1999) found that the addition of mature students into their geo-demographic analysis of participation did not equalise the gap in entry rates. An important barrier to the inclusion of older entrants in the analysis is the lack of available data on those aged over 21.…”
Section: Discussionmentioning
confidence: 92%
“…Robertson and Hillman suggest that a more articulated system of post-compulsory qualifications, characterised by greater flexibility and ease of transfer between different sectors, would go some way towards reducing structural inequalities. Furthermore, Johnston et al (1999) found evidence of cultural influences on young people's behaviour, whereby those who lived in areas where higher education was not the norm were less likely to participate. They showed that average levels of education and unemployment in the local area influenced participation over and above the influence of individual economic factors.…”
Section: Social Background and Higher Education In Scotland 369mentioning
confidence: 99%
“…5 The Dearing Report emphasizes widening access to HE through increasing the participation of under-represented groups. This is part of a long history of calls for a reduction in social inequalities in HE participation rates (Johnston, Raab & Abdalla, 1999) and was reflected in the Robbins Report (1963) that led to the setting up of the new universities in the 1960s and the first UK distance learning university-the Open University. The Dearing Report asks that ' .…”
Section: He and The Dearing Reportmentioning
confidence: 99%
“…It has been argued elsewhere (Comer, 1976(Comer, , 1987) that schools do not serve their students well when they are in disjuncture with their surrounding communities. Typically, those who have become tutors in the HE sector have come from a predominantly white, male, non-disabled middle-class background while non-dominant groups still face barriers in gaining access to HE as students (Johnston et al, 1999;Power, 2000;THES, 1998;Tysome, 2000). Despite the climate of widening access few universities have adequate equal opportunities policies and fewer monitor their equal opportunities practices (Thanki & Osborne, 2000).…”
Section: Social Democratic Social Policy and Third-way Politicsmentioning
confidence: 99%
“…The apparent marked increase in interest in pursuing a degree amongst current HN learners is possibly a direct result of various programmes (e.g. raising achievement, lifelong learning) that are intended to impact upon learners' educational aspirations (Johnston 2003;Elliot and Kerr 2005;SFC 2007). Equally, learners already in education are more likely to continue, whilst those who have completed their studies and moved on to other things are less likely to return to education.…”
Section: Learner Progression After College Studiesmentioning
confidence: 99%